Roots of Tropical Polynomial from Clopen and Non-Clopen Discrete m-Topological Transformation Semigroup - O Francis, M.; F. Joseph, L.; T. Cole, A.; Oshatuyi, B. (International Journal of Advanced Mathematical Sciences, 2024)
This paper introduces a specific subclass of m-topological transformation semigroup spaces, referred to as closed m-topological full transformation semigroup spaces. It defines both the clopen and non-clopen elements within these spaces and explores the nature of their roots. The study presents formulas for clopen and non-clopen elements, as well as for the closed m-topological full transformation semigroup spaces. Furthermore, numerical and graphical results for degrees 2 and 3 are provided to illustrate the findings.